2014
DOI: 10.1136/injuryprev-2014-041328
|View full text |Cite
|
Sign up to set email alerts
|

Effects of racing games on risky driving behaviour, and the significance of personality and physiological data

Abstract: The effect of playing racing games on risk-taking inclination is linked to personality and physiological data. Some recommendations are proposed as a result of this study for racing game management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…Finally, after screening, 22 out of the 2261 published studies were included in our meta-analysis. 6,15-23,32-43 The studies were published between 1994 and 2017. These 22 selected studies included 11211 participants; with a median number of 260 (range: 40-2604) participants per study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, after screening, 22 out of the 2261 published studies were included in our meta-analysis. 6,15-23,32-43 The studies were published between 1994 and 2017. These 22 selected studies included 11211 participants; with a median number of 260 (range: 40-2604) participants per study.…”
Section: Resultsmentioning
confidence: 99%
“…15 Of the many PCs identified as potential predictors of RDBs, the big five personality factors (including extraversion, agreeableness, conscientiousness, neuroticism, and openness), sensation seeking, and driving anger have garnered the most support to date. 16 However, despite the fact that several studies have reported significant correlations (positive/negative) between PCs and RDBs, 16-19 a number of other studies did not find RBDs were significantly related to PCs, such as: agreeableness, 20 neuroticism, 6 extraversion, 20 openness, 21 sensation seeking, 22 and driving anger. 23 In a meta-analysis conducted by Demir et al 24 they reported that driving anger had significant associations with aberrant driving behaviors (based on Driver Behavior Questionnaire - DBQ) factors.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The main advantage of this approach is to provide a realistic but safe environment, free from any real threat, that makes the patients more inclined to accept the treatment (there are no real spiders during the treatment or, in the case of acrophobia, no real cliffs), but that still triggers real manifestations of fear. On the opposite, it could be argued that because there are no real consequences to a virtual action, dangerous behaviors devoid of any concrete negative consequence could be promoted and applied to the real life, as in the example of reckless driving in video games (there are no real consequences to a virtual car crash) ( 46 ). The use of virtual avatars could also be helpful in psychiatric treatments, as, for example, evidenced by a recent study that demonstrated how using avatar-based therapy is useful to decrease persecutory auditory hallucinations ( 47 ).…”
Section: Games Are Virtualmentioning
confidence: 99%
“…Deng and colleagues ([ 22 ]—experiment 1) used a student sample to determine whether VRGs influence risk-favourable attitudes. The role of personality traits was also investigated.…”
Section: Introductionmentioning
confidence: 99%